Selective removal of apolipoprotein B-containing serum lipoproteins from blood plasma. - Stoffel, W (1981)
Studies were undertaken to determine the applicability and effectiveness of immunoadsorption chromatography on anti-low density lipoprotein (LDL) columns as a plasma-cholesterol-lowering procedure. Mass production and isolation of monospecific antibodies against swine LDL (rho = 1.006-1.063 g/ml) was carried out by immunization of sheep with swine LDL and selective antibody adsorption from their antisera by chromatography on LDL-Sepharose. The isolated LDL antibodies were then covalently linked to Sepharose CL-4B. Pig plasma LDL was effectively removed in vitro by the anti-LDL-Sepharose beads. In vivo studies were performed in pigs with (i) a plasma-separator membrane permeable to solutes below Mr 2,000,000 or (ii) a blood centrifuge interposed into an arteriovenous shunt to separate the corpuscular elements of blood from the plasma. In either case, the plasma was passed through the anti-LDL-Sepharose column and recirculated into the venous part of the shunt. Plasma cholesterol levels were reduced 70-80% by this procedure and rebounded 3-4 days after the extracorporeal immunoadsorption procedure. This continuous plasma separation-immunoadsorption procedure may have broad applicability for the elimination of any plasma component with antigenic properties.